Optimal Control for Sport Utility Vehicle System Using Linear Quadratic Integral Control Approach - Omar, M. F.; Ghazali, R.; Saadon, I. M.; Aripin, M. K.; Sam, Y. M.; Soon, C. C. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The Sport Utility Vehicle (SUV) has become one of the popular vehicles to be chosen, since it was first introduced. However, the higher Centre of Gravity (C.G) and the bigger sizing at the side area have led to the stability and the handling issues that degrade the vehicle’s performances, especially during the confrontation with external disturbances. This paper presents an analysis of an optimal control that enhances the handling and stability of the SUV. The Direct Yaw Control (DYC) method was used to control the vehicle’s accuracy and robustness towards environmental parameters during the critical manoeuvre. The Linear Quadratic Regulator (LQR) and Linear Quadratic Integral (LQI) were compared to obtain the optimal performances during the control of the vehicle’s handling and stability. With the interference of an external disturbance during the critical manoeuvre, the results indicate that the LQI produce significant improvement in the vehicle’s handling and stability control.